Prevalence of lice infestation in alpaca crias from the southern Peruvian Andes - Gomez‐Puerta, Luis A.; Carrasco, Johan; Garcia, Madeline; Lopez‐Urbina, Maria T.; Gavidia, Cesar M. (Medical and veterinary entomology, 2025)
Lice are very common ectoparasites of humans and other animals. These ectoparasites cause various health problems in the hosts, like alpacas, such as intense itching, skin irritation, hair or wool loss, anaemia, and, in severe cases, reduced milk and meat production due to the stress they cause in the host. Epidemiological studies in alpacas are necessary to determine the magnitude and distribution of lice infestation, which would assist in the implementation of control measures. The aim of this study was to determine the prevalence of lice infestation in newborn and young alpacas (crias) from the provinces of Canchis and Espinar, located in the southern Peruvian Andes. Veterinarians examined a total of 383 alpaca crias less than 6 months of age to diagnose lice infestation. Lice were collected and preserved in 80% ethanol for morphological diagnosis. Also, all animal data such as sex, breed, province, and herd size were recorded for analysis. Lice were detected in 352 out of 383 (91.9%; confidence interval (CI 95% ) = 88.7%–94.4%) alpaca crias, and three species of lice were identified: two Anoplura from the Microthoraciidae family corresponding to Microthoracius praelongiceps (Neumann, 1909) (91.9%; 353/383) and M . mazzai Werneck, 1932 (18.5%; 71/383), and one Mallophaga from the Trichodectidae family corresponding to Bovicola breviceps (Rudow, 1866) (11.5%; 44/383). The parasite load was very high, especially in the areas of the neck, arms, legs, armpits, and groin in the infested animals. Only the infestation for M. praelongiceps was associated with provinces but not with other variables. M . mazzai and B. breviceps infestations were not associated with any variable. Future epidemiological studies will be necessary to better understand the interactions between the species of lice and risk factors such as local characteristics and livestock husbandry, as well as the negative effect caused by this parasitism in alpacas. Los piojos son ectoparásitos muy comunes en humanos y otros animales. Estos ectoparásitos causan diversos problemas de salud en los hospederos, como las alpacas, como picazón intensa, irritación de la piel, pérdida de pelo o lana, anemia y, en casos graves, reducción de la producción de leche y carne debido al estrés que les causan. Se requieren estudios epidemiológicos en alpacas para determinar la magnitud y distribución de la infestación por piojos, lo cual facilitaría la implementación de medidas de control. El objetivo de este estudio fue determinar la prevalencia de la infestación por piojos en crías alpacas de las provincias de Canchis y Espinar, ubicadas en los Andes del sur del Perú. Los veterinarios examinaron un total de 383 crías de alpacas menores de 6 meses de edad para diagnosticar la infestación por piojos. Los piojos se recolectaron y conservaron en etanol al 80% para el diagnóstico morfológico. Además, se registraron todos los datos de los animales, como sexo, raza, provincia y tamaño del rebaño, para su análisis. Se detectaron piojos en 352 de 383 crías de alpaca (91.9%; intervalo de confianza (IC 95% ) = 88.7%–94.4%) y se identificaron tres especies de piojos: dos Anoplura de la familia Microthoraciidae correspondientes a Microthoracius praelongiceps (Neumann, 1909) (91.9%; 353/383) y M. mazzai Werneck, 1932 (18.5%; 71/383) y un Mallophaga de la familia Trichodectidae correspondiente a Bovicola breviceps (Rudow, 1866) (11.5%; 44/383). La carga parasitaria fue muy alta, especialmente en las áreas del cuello, brazos, piernas, axilas e ingles de los animales infestados. Solo la infestación por M. praelongiceps se asoció con las provincias, pero no con otras variables. La infestación por M. mazzai y B. breviceps no se asociaron con ninguna variable. Se necesitarán más estudios epidemiológicos en el futuro para entender mejor cómo interactúan las especies de piojos con factores de riesgo como las características locales y la ganadería, además del daño que este parasitismo causa en las alpacas.